Documentation of plant-based food wrapper utilised by communities in Bintulu, Sarawak - Yusli, Nurul Aisyah; Saupi, Noorasmah; Dadi, Samantha Natalie (Malaysian Society of Applied Biology, 2023)
Usage of wrapping or packaging is very significant in food processing to protect, secure, and provide a specific image of the food contained. Around 10,000 years ago, food wrappers were developed by our ancestors using natural substances such as animal skins, tree stems, and leaves. There is limited information on food wrappers based on Sarawaks natural resources. However, among the older Sarawak communities, such knowledge is present and valuable. Unfortunately, this information is on the verge of extinction due to a lack of documentary. Therefore, this study was conducted to identify and document the plant-based food wrappers used by the communities in Sarawak. An ethnobotanical study was conducted using face-to-face interviews with 384 respondents. The study was conducted in a semi-structured manner from December 2021 until May 2022. A total of 21 species of plants from 11 different families has been identified as food wrapper by the community in Bintulu, Sarawak. The community dominantly used leaves as food wrappers because they can be handled easily and enhance the aroma of the food. Some plant-based food wrapper gives a distinct flavor and aroma to the food when applied with heat. Plantbased food wrappers also had huge potential as more than 90 of respondents were satisfied with the usage and suggested that these wrappers be developed into ready-made form. Locals also informed that plant-based food wrappers can help to expand their economic profit, especially for sellers. Therefore, this study was able to discover the indigenous plant species utilized as traditional food wrappers that have been forgotten. However, further study about the nutritional composition, fiber structure, antibacterial ability, and volatile compound of the species can be conducted to provide a full record of the plants, especially as food aroma enhancers.